Association of the DVWA and GDF5 polymorphisms with osteoarthritis in UK populations. Issue 12 (3rd December 2008) - Valdes, A M; Spector, T D; Doherty, S; Wheeler, M; Hart, D J; Doherty, M
Abstract : Background: Variants in the growth differentiation factor 5 ( GDF5 ) and in the double von Willebrand factor A ( DVWA ) have recently been reported to be associated with osteoarthritis (OA) in Asian populations. Objective: To assess the role of such variants in OA susceptibility in two independent UK samples of Caucasian origin. Methods: Polymorphisms rs11718863 and rs7639618 ( DVWA ) and rs143383 ( GDF5 ) were genotyped in 999 patients with knee OA, 843 patients with hip OA and 1166 controls from two UK studies from Nottingham and Chingford. Results: In agreement with previous reports, the major allele at rs143383 ( GDF5 ) was associated with a higher risk of knee OA in our samples (ORMH  = 1.29, 95% CI 1.14 to 1.47 p = 8×10 −5 ). Conversely, the major allele at the DVWA SNP rs7639618, which increased risk in Asians, was not associated with a risk of knee OA, (ORMH  = 0.88, 95% CI 0.74 to 1.04; p = 0.12). A meta-analysis of Asian and UK knee OA data indicated highly significant heterogeneity ( I 2  = 92%, Q  = 48.5, p = 7×10 −10 ) and no significant association with knee OA using a random effects meta-analysis (ORDL  = 1.18, 95% CI 0.86 to 1.63; p = 0.309). Conclusions: These data confirm that the GDF5 variant is consistently associated with the risk of knee OA. Considerable ethnic variation in allele frequencies at the DVWA gene was found and no significant association was found in UK samples or by combining UK and Asian samples. The results suggest that the effect of DVWA amino acid changes on tubulin binding is unlikely to influence the risk of OA in Caucasians.